Strategi Pengelolaan Panti Asuhan dalam meningkatkan Kesejahteraan Anak Asuh di Asrama Sahabat Yatim Medan Aksara - N, Nurmayani; Haliza, Putri Yusra; Sarah, Auta Shintha; Faradhilah, Anatasia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
A good and correct orphan management system greatly affects the fate and future of orphans. The welfare of orphans is not only measured physically, but also mentally and spiritually. This study aims to understand the strategies, programs and challenges faced by the Sahabat Yatim Medan Aksara Orphanage and then provide solutions to any challenges faced. The research method used is a qualitative approach method by conducting interviews with caregivers, foster children, and management staff. Direct observation was conducted to see how the rules are applied, the availability of supporting facilities, the physical and psychological well-being of foster children, and the relationship between foster children and caregivers. The results showed that Sahabat Yatim Medan Aksara Orphanage has implemented rules, provided facilities for education and daily needs but still faced several challenges. Overall, the quality of life of foster children has been improved physically, mentally, and spiritually through good management and a comprehensive welfare program.